Faktor-Faktor yang Mempengaruhi Organizational Commitment pada Karyawan Kementrian Pariwisata dan Ekonomi Kreatif di Jakarta - Putri, Sasikirana Zahra; Berliyanti, Dita Oki (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
The purpose of this study is to analyze the influence of Knowledge Sharing and Life Satisfaction on Organizational Commitment, mediated by Job Performance at the Ministry of Tourism and Creative Economy. Data was collected from 142 employees of the Ministry of Tourism and Creative Economy in Jakarta using the Snowball Sampling technique. The analytical method used in this research is the Structural Equation Model (SEM) version 26 and SPSS version 27. Prior to analysis, the instruments were tested for validity and reliability, where all statements were found to be valid and reliable. The model was also tested using the Goodness of Fit. The results of the study indicate that Knowledge Sharing has a positive effect on Organizational Commitment, Knowledge Sharing has a positive effect on Job Performance, Life Satisfaction has a positive effect on Job Performance, and Life Satisfaction does not have a positive effect on Organizational Commitment. Job Performance has a positive effect on Organizational Commitment. Regarding the mediation role, Job Performance can partially mediate the influence of Knowledge Sharing on Organizational Commitment, and Job Performance can also partially mediate the influence of Life Satisfaction on Organizational Commitment. The managerial implications of this research suggest that management can take strategic steps to foster a culture of knowledge sharing through training, workshops, and digital platforms. Management should also enhance employees' emotional well-being through counseling programs and recreational activities to support life satisfaction. In addition, the development of skills, regular performance evaluations, feedback, and rewards can improve employee performance and commitment.